Gut Microbiota Alteration Is Associated With Cognitive Deficits in Genetically Diabetic (Db/db) Mice During Aging - Zhang, Jiawei; Zhang, Yaxuan; Yuan, Yuan; Liu, Lan; Zhao, Yuwu; Wang, Xiuzhe (Frontiers in Aging Neuroscience, 2022)
Recent studies have revealed that the microbiota may be implicated in diabetes-related cognitive dysfunction. However, the relationship between gut microbiota and cognitive dysfunction during the progression of type 2 diabetes remains elusive. We used 16S rRNA sequencing combined with conventional behavioral tests to explore the longitudinal changes of gut microbiota and cognition in diabetic db/db mice (leptin receptor knockout mice) and their wild-type littermates at different ages. Prussian blue staining was performed to detect the microhemorrhage in the brain, and immunofluorescent study was applied to analyse microglia activation. Moreover, a Meso Scale Discovery kit was used to determine the cytokine levels in the brain. Db/db mice exhibited age dependent pathological characteristics, including cognitive deficits, neuron damage, spontaneous hemorrhages and neuroinflammation. Moreover, we observed that the diversity and composition of gut microbiota significantly differed between the wild-type and db/db mice during aging. We found that compared to age-matched wild-type mice, genus Helicobacter was significant higher in db/db mice at 18 and 26 weeks. Correlation analysis revealed that Helicobacter is positively associated with Iba-1 positive cells and TNF-α expression. Collectively, our longitudinal study suggests that diabetic cognitive impairment during aging is associated with abnormal gut microbiota composition, which may play a role in the regulation of neuroinflammation.